2009
DOI: 10.3748/wjg.15.467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative immunonutrition and other nutrition models on cellular immune parameters

Abstract: AIM:To e va l u a t e t h e e f fe c t s o f p r e o p e ra t i v e immunonutrition and other nutrition models on the cellular immunity parameters of patients with gastrointestinal tumors before surgical intervention. In addition, effects on postoperative complications were examined. METHODS:Patients with gastrointestinal tumors were randomized into 3 groups. The immunonutrition group received a combination of arginine, fatty acids and nucleotides. The second and third group received normal nutrition and stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 28 publications
0
81
0
2
Order By: Relevance
“…to bring about a decrease in T-lymphocytes and natural killer cells (2) . The result of this suppression is an increased risk of infection.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…to bring about a decrease in T-lymphocytes and natural killer cells (2) . The result of this suppression is an increased risk of infection.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…13,[21][22][23][24][25][26][27][28][29] In the present study, we enrolled all patients at nutritional risk who were identified by using the NRS, and no restriction on the type of operation was made, as this patient group is likely to benefit most from nutritional interventions. [6][7][8] So far, no randomized trial on IN has used the NRS before.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of protein greater than 20% due to a negative impact on the structure and function of the respiratory muscles and lung parenchyma leads to a reduction in weight and respiratory muscle strength, reduces neuronal respiratory drive, and causes abnormal ventilation, prolonged respiratory therapy and increased risk of infection. Malnutrition through a range of mechanisms leads to weakening of the immune defense of the body: it causes atrophy of lymph nodes, inhibits the maturation and differentiation of lymphocytes, reduces the secretion of IgA, and suppresses the cellular response [13]. Very important is the local effect of nutrition in the gastrointestinal tract and its impact on the body's defense mechanisms.…”
Section: Malnutritionmentioning
confidence: 99%
“…Loss of 10% of ideal body weight within 3-4 months leads to changes in function of the immune system. It is described that among patients with diagnosed cancer of the gastrointestinal tract 90% were malnourished [13,15]. Energy requirement is estimated based on anthropometric data: age, sex, weight, height, and markers of the metabolic consumption of O 2 and generation of CO 2 .…”
Section: Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation